1988
DOI: 10.7326/0003-4819-109-11-870
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mass Is Low in Relatives of Osteoporotic Patients

Abstract: Mean bone mass is lower in apparently healthy young and middle-aged adult relatives of osteoporotic patients than in normal persons with no family history of osteoporosis. Our findings suggest that the failure to attain an adequate peak bone mass may play an important role in the later development of osteoporotic fractures. Relatives of osteoporotic patients should be advised to have measurements of bone mass taken. This measurement should be taken at the spine, because peripheral sites do not appear to provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(59 citation statements)
references
References 7 publications
4
53
0
2
Order By: Relevance
“…Lower BMD among the premenopausal daughters could translate to higher fracture risk in the future and certainly reinforces the need for prevention and early risk assessment, particularly among women with a positive family history. Our findings are consistent with several studies which compared bone mass among relatives with and without a family history of fracture or osteoporosis (6,(14)(15)(16)(17) but contrary to some others that found no increase in the prevalence of low bone mass, (5) vertebral deformity, (18) or fracture (33) among female offspring of women with osteoporotic fracture. Differences in sample selection, age of study participants, or fracture definition have been cited as possible reasons for the discrepant findings.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Lower BMD among the premenopausal daughters could translate to higher fracture risk in the future and certainly reinforces the need for prevention and early risk assessment, particularly among women with a positive family history. Our findings are consistent with several studies which compared bone mass among relatives with and without a family history of fracture or osteoporosis (6,(14)(15)(16)(17) but contrary to some others that found no increase in the prevalence of low bone mass, (5) vertebral deformity, (18) or fracture (33) among female offspring of women with osteoporotic fracture. Differences in sample selection, age of study participants, or fracture definition have been cited as possible reasons for the discrepant findings.…”
Section: Discussionsupporting
confidence: 82%
“…(3) Previous studies have reported significant and relatively consistent parent-offspring correlations in bone mineral density (BMD) (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) and have shown that a family history of osteoporosis and/or fracture is associated with an increased risk of low BMD and fracture. (14)(15)(16)(17)(18)(19) Some, (14,16) but not all, (6,13,(17)(18)(19) of these studies confirmed a family history of osteoporosis or fracture via medical records or radiographs. Only a few studies have addressed the potential influence of ''heritable'' lifestyle factors on familial association in bone mass.…”
Section: Introductionmentioning
confidence: 69%
“…The time interval between the attainment of peak aBMD in the second or third decade and the occurrence of vertebral fractures more than 3 decades later probably precludes prospective evaluation of the relative contribution of reduced peak aBMD to the deficit in aBMD in patients with fractures. Nevertheless, some insight has been obtained from studies of the familial resemblance of aBMD in patients with fractures and in their offspring (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…63 Heritability studies show that genetic factors may account for 50-80% of the variance in BMD. 64,65 The canonical Wnt pathway is critical for skeletal development and maintenance, though the precise roles of Wnt co-receptors LRP5/6 are not entirely clear. Approximately a decade ago, the identification of causal mutations in LRP5 involved in two rare bone disorders propelled research in the bone area into completely new directions.…”
Section: Lrp6 Genetic Polymorphisms and Osteoporosismentioning
confidence: 99%